Comparison of channel mobility and oxide properties of MOSFET devices on Si-face (0001) and A-face (11-20) 4H-SiC. Issue 1693 (4th June 2014) - Lichtenwalner, Daniel J.; Cheng, Lin; Allen, Scott; Palmour, John W.; Lelis, Aivars; Scozzie, Charles
ABSTRACT: In this report we present results comparing lateral MOSFET properties of devices fabricated on Si-face (0001) and A-face (11-20) 4H-SiC, with nitric oxide passivation anneals. We observe a field-effect mobility of 33 cm 2 /V.s on p-type 5×10 15 doped Si-face. These devices have a peak field-effect mobility which increases with temperature, indicative of a channel mobility limited by coulomb scattering. On 1×10 16 p-type A-face SiC, the peak channel mobility is observed to be 80 cm 2 /V.s, with a negative temperature dependence, indicating that phonon-scattering effects dominate, with a much lower density of shallow acceptor traps. This > 2x higher channel mobility would result in a substantial decrease in on-resistance, hence lower power losses, for 4H-SiC power MOSFETs with voltage ratings below 2 kV. However, MOS C-V and gate leakage measurements indicate very different oxide and interface quality on each SiC face. For example, the Fowler-Nordheim (FN) conduction-band (CB) barrier height for electron tunneling at the SiO2 /SiC interface is 2.8 eV on Si-face SiC, while it is 2.5 eV or less on A-face SiC. For the valence-band side, the effective FN barrier height at the valence-band (VB) side of only 1.6 eV on A-face SiC, while the VB barrier height is about 3.1 eV on Si-face SiC. Moreover, C-V of the MOS gate on A-face indicates the presence of a high-density of deep hole traps. It is apparent that oxides on alternative crystal faces, very promising in terms of channel mobility, require further study for complete understanding and control of the interface properties.